Upper Gastrointestinal Bleeding Secondary to an Aberrant Right Subclavian Artery-Esophageal Fistula: A Case Report and Review of the Literature - Adam Millar; Alaa Rostom; Pasteur Rasuli; Nav Saloojee (Canadian Journal of Gastroenterology)
An aberrant right subclavian artery (ARSA) is a common aortic arch abnormality. A case of a 57-year-old man presenting with melena and hypotension secondary to an ARSA-esophageal fistula is reported. The current report is unique because it is the first reported case of ARSA-esophageal fistula associated with prior esophagectomy and gastric pull-up. A MedLine search was performed for ARSA-esophageal fistula cases, which were then compared with the present case. Because this patient had no vascular conduits, nasogastric or endotracheal tubes, the fistula likely occurred secondary to the previous surgery. This case is unusual because the patient survived the original hemorrhage associated with the ARSA-esophageal fistula.